Improving Quality of Life for Patients with Cerebral Palsy: Evidence-Based Nursing Strategies - Abdulaziz Haasan Alanazi, Abdullah Mohammed Alanazi, Adel Salem Alenazi, Alhanouf Mohammed Alanazi, Atheer Alwanci Saleh Alruwaili, Seba Saleh Alabdali, Ibtesam Eid ALanzi, Asma Mohammed Alabdli (Journal of International Crisis and Risk Communication Research, 2024)
Cerebral palsy (CP) is a complex and multifaceted condition that affects individuals from infancy through adulthood, presenting unique challenges that can significantly impact their quality of life. As a group of permanent movement disorders caused by non-progressive disturbances in the developing brain, CP encompasses a range of motor impairments, often accompanied by sensory, cognitive, and emotional challenges. The role of nursing in improving the quality of life for patients with cerebral palsy is critical, as nurses are often the primary caregivers who provide continuous support and advocacy for these individuals and their families. This article explores evidence-based nursing strategies that can enhance the quality of life for patients with cerebral palsy, focusing on holistic care, therapeutic interventions, psychosocial support, and the importance of family involvement. A comprehensive approach to care is essential, considering the physical, emotional, and social dimensions of health. Therapeutic interventions, such as physical therapy, occupational therapy, speech and language therapy, and the use of assistive technology, can improve functional abilities and promote independence. Psychosocial support is also crucial, addressing the emotional and social challenges faced by individuals with CP. Family-centered care is another essential component of nursing practice, recognizing that a strong support system is vital for the well-being of both patients and their caregivers. Nurses should educate families about cerebral palsy, providing them with information about the condition, available resources, and strategies for supporting their loved ones. By fostering open communication and collaboration with families, nurses can create a supportive environment that promotes the well-being of both patients and their caregivers. The implementation of evidence-based nursing strategies can significantly improve the quality of life for patients with cerebral palsy. By adopting a holisticapproach to care, nurses can empower individuals with CP to achieve their fullest potential and enhance their overall well-being. This article provides a comprehensive overview of the evidence-based nursing strategies that can improve the lives of patients with cerebral palsy, highlighting the critical role of nurses in promoting positive outcomes for these individuals and their families.